Domain glass. Issue 10 (25th January 2014) - Salje, E. K. H.; Ding, X.; Aktas, O.
<x xml:space="preserve">Abstract</x> Microstructural patterns of twin boundaries and tweed in ferroelastic materials display typical aspects of glasses. The patterns are complex, their dynamics follows Vogel–Fulcher statistics and their field cooling–non‐field cooling hysteresis is similar to those described in this issue as 'strain glasses'. The difference is that domain glasses do not need extrinsic defects to form. In the paraelastic phase, an intrinsic tweed pattern dominates the high temperature precursor regime. Experimentally, massive elastic precursor softening is related to polar standing waves, which are attributed to the glassy relaxation of the tweed pattern. In the ferroelastic phase we find a complex twin pattern when the sample is strained with a constant strain rate. The dynamics of the pattern formation is a‐thermal at low temperatures and follows Vogel–Fulcher statistics at moderately high temperatures. It is argued that domain boundary patterns can hence evolve glass‐like states while the underlying matrix remains fully crystalline without any defect induced disorder.